Endoscopic removal of a retained surgical sponge in a young Syrian refugee after Caesarean section: a case report with discussion of cultural and political consequences. Issue 1 (December 2016) - Ackermann, Johannes; Kanzow, Moritz; Mathiak, Micaela; Pecks, Ulrich; Maass, Nicolai; Alkatout, Ibrahim
Abstract Background Inadvertently retained sponges and instruments still constitute a major but preventable complication in surgery. Given the high geographic mobility of patients, the fluctuation of physician-patient contact, and communication problems due to language barriers, the conscientious use of structured safety protocols in clinical routine is an essential aspect of quality in health care. Case presentation We report the case of a 24-year-old refugee from Syria who presented at our gynecological outpatient department with a tumor in the lower abdomen, suspected to be a lump in the ovary or the uterus. Language barriers hindered exact recording of the patient's medical history. We knew she had undergone three Caesarean sections several years ago. The diagnostic laparoscopy unexpectedly revealed a tumor suspected to be a retained surgical sponge. The lesion was removed completely and the patient discharged from the clinic five days later. Conclusion In ambiguous cases, the diagnostic and therapeutic potential of minimally invasive surgery ensures safe and effective treatment of the patient, a short hospital stay, and low rates of complications. Especially in cases of language and/or cultural barriers, structured safety protocols should be a part of clinical routine in order to prevent unnecessary complications.